Exploring narcissism and human- and animal-centered empathy in pet owners - Giacomin, Miranda; Johnston, Emma E.; Legge, Eric L. G. (Frontiers in Psychology, 2023)
Having empathy for others is typically generalized to having empathy for animals. However, empathy for humans and for animals are only weakly correlated. Thus, some individuals may have low human-centered empathy but have high animal-centered empathy. Here, we explore whether pet owners who are high in narcissism display empathy towards animals despite their low human-centered empathy. We assessed pet owners’ (N = 259) three components of trait narcissism (Agentic Extraversion, Antagonism, and Narcissistic Neuroticism), human- and animal-centered empathy, attitudes towards animals, and their pet attachment. We found that Agentic Extraversion was unrelated to both human- and animal-centered empathy. We also found that Antagonism was related to less empathy for both humans and animals, as well as more negative attitudes towards animals. Lastly, we found that Narcissistic Neuroticism was unrelated to human-centered empathy and positively related to animal-centered empathy and attitudes towards animals. This research furthers our understanding of the relation between empathy towards humans and animals and provides insight into whether animal-assisted approaches may be useful for empathy training in those with narcissistic characteristics.